5 The Impact of Psychiatric Comorbidities on the Length of Hospital Stay in Patients with Heart Failure. (3rd June 2016) - Carter, Paul; Carter, Andrew; Reynolds, Jennifer; Uppal, Hardeep; Chandran, Suresh; Potluri, Rahul
Abstract : Introduction: Heart failure (HF) is a major healthcare problem contributing significantly to hospital admission stays and NHS spending. Reducing length of hospital stay (LOS) in HF is paramount in reducing this burden and is influenced by factors relating to the condition, sociodemographics and comorbidities. Psychiatric comorbidities are being increasingly identified amongst HF patients but their impact on LOS has not been studied in the UK. Objectives: We aimed to investigate the impact of psychiatric comorbidities on length of hospital stay in a large database of patients admitted with heart failure to hospitals in the North of England over a 14-year period between 2000–2013. Methods: Anonymous information on heart failure patients was obtained from the local health authority hospital activity register for hospitals in North West England between 1st January 2000 and 31 st March 2013. This data was analysed according to the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol. ICD-10 and OPCS-4 codes were used to trace HF patients, psychiatric comorbidities and demographics including LOS. LOS of HF patients with and without psychiatric comorbidites were compared by logistic regression. P values of <0.05 were taken as statistically significant. Results: Of 929552 patients admitted during the study period 31760 patients had heart failure. The mean age of heart failure patients was 73.6, 50.3% were male and the majority were of Caucasian origin (85.1%). Amongst 31760 HF patients mean LOS in the absence of psychiatric comorbidities was 11.2 days. Presence of a psychiatric comorbidity increased LOS by 3.3 days. Logistic regression accounting for age, gender and ethnicity showed that LOS was significantly longer in patients suffering from depression (3.4 days), bipolar disorder (8.8 days), dementia (4.2 days), dementia unspecified (4.6 days) and vascular dementia (3.0 days). Conversely, LOS was significantly reduced by 3.7 days in patients with comorbid tobacco abuse. Conclusion: Our results demonstrate that psychiatric comorbidities have a significant and clinically important impact on LOS in HF patients in the UK. Clinicians should be actively aware of psychiatric conditions amongst HF patients and manage them to reduce LOS and ultimately the risk for patients and financial burden for the NHS.